2015
DOI: 10.1063/1.4914296
|View full text |Cite
|
Sign up to set email alerts
|

Performance regeneration of InGaZnO transistors with ultra-thin channels

Abstract: Thin-film transistors (TFTs) based on ultra-thin amorphous indium gallium zinc oxide (a-IGZO) semiconductors down to 4 nm were studied motivated by the increasing cost of indium. At and below 5 nm, it was found that the field-effect mobility was severely degraded, the threshold voltage increased, and the output characteristics became abnormal showing no saturated current. By encapsulating a layer of polymethyl methacrylate on the IGZO TFTs, the performance of the 5-nm-thick device was effectively recovered. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…The subthreshold threshold, SS, is about 0.63V/dec, as extracted from the linear extrapolation of the transfer curve in log scale. The channel trap density Dt is extracted by evaluation of SS as follows [25]: (1) where q is the electron charge, kB is the Boltzmann constant, T is the absolute temperature, and Cox is the gate capacitance per unit area. By Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The subthreshold threshold, SS, is about 0.63V/dec, as extracted from the linear extrapolation of the transfer curve in log scale. The channel trap density Dt is extracted by evaluation of SS as follows [25]: (1) where q is the electron charge, kB is the Boltzmann constant, T is the absolute temperature, and Cox is the gate capacitance per unit area. By Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The estimated contact resistance of the device is less than 10% of the total channel resistance, even at V G = 1 V. It is also found that I D exhibits a clear pinch off and saturates at higher V D . A slight decrease of I D is observed in the saturation regime, which might be caused by a hot carrier effect and/or selfheating effects [25][26][27][28]. Under such effects, charge trapping occurs, resulting in a positive threshold voltage shift and a slight decrease in I D .…”
Section: Introductionmentioning
confidence: 99%
“…After that, a-IGZO has received much attention because of its excellent performance, including high electron mobility, low off current, excellent uniformity, surface flatness, stability, optical transparency, large-area production, and wide process temperature. 5,6 As such, a-IGZO TFTs have started replacing amorphous-silicon transistors in large-area displays. 7,8 However, large voltages are often needed for a-IGZO TFTs to achieve high mobility and high on/off current ratios.…”
mentioning
confidence: 99%